2014
DOI: 10.1016/j.jom.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐solving effort and success in innovation contests: The role of national wealth and national culture

Abstract: Please cite this article in press as: Bockstedt, J., et al., Problem-solving effort and success in innovation contests: The role of national wealth and national culture. J. Operations Manage. (2015), http://dx. a b s t r a c tInnovation contests allow firms to harness specialized skills and services from globally dispersed participants for solutions to business problems. Such contests provide a rich setting for operations management (OM) scholars to explore problem solving in global labor markets as firms cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 75 publications
(110 reference statements)
3
68
0
Order By: Relevance
“…These contrasting results can be explained by an interaction effect among culture and contextual variables. Wiengarten et al (2015) found an interaction effect between national and organisational culture, and Bockstedt, Druehl, and Mishra (2015) noted that cultural influence is weakened by national wealth. Overall, this finding supports our second conclusion in Section 4.1, and it is in line with the conclusions drawn in Sections 4.2.1 and 4.2.2 regarding the importance of including contextual conditions in the analysis of the impact of national culture because they can influence the strength and direction of culture-practice relationships.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…These contrasting results can be explained by an interaction effect among culture and contextual variables. Wiengarten et al (2015) found an interaction effect between national and organisational culture, and Bockstedt, Druehl, and Mishra (2015) noted that cultural influence is weakened by national wealth. Overall, this finding supports our second conclusion in Section 4.1, and it is in line with the conclusions drawn in Sections 4.2.1 and 4.2.2 regarding the importance of including contextual conditions in the analysis of the impact of national culture because they can influence the strength and direction of culture-practice relationships.…”
Section: 23mentioning
confidence: 99%
“…Some authors have found that organisational culture weakens the effects of national culture on OM strategy (Naor, Linderman, and Schroeder 2010) and OM improvement (Wiengarten et al 2015). National wealth reduces the impact of culture on OM improvement (Bockstedt, Druehl, and Mishra 2015), and the national regulations limit the influence of culture on OM strategy (Fredendall, Letmathe, and Uebe-Emden 2016). Other contextual variables were included as control variables in some reviewed articles, but these did not have an interaction effect with culture.…”
Section: Interplay Of National Culture and Contextual Variablesmentioning
confidence: 99%
“…Many researchers have investigated the implications of architectural decisions that are made at the outset of a contest. These decisions include, among others, the award structure (Bull et al 1987, Liu et al 2014, the number of solvers (Garcia and Tor 2009, Boudreau et al 2011, Lim et al 2014), talent differences (Schotter and Weigelt 1992, Fonseca 2009, Jeppesen and Lakhani 2010, Bockstedt et al 2015, the distribution of information (Brookins and Ryvkin 2014), and problem uncertainty (Boudreau et al 2011). More recently, researchers have begun to pay closer attention to decisions that are made in the course of a contest.…”
Section: Related Literaturementioning
confidence: 99%
“…The Rituals and Stories regarding innovations showed positive relations with four types of innovation, corroborating hypothesis H1b. This reinforces the importance of the theme according to the literature in the area, emphasizing the need for stories in the organizational culture as an interpretation of the reality in the same way that rites reinforce group mythology (Pettigrew, 1979;Jarnagin & Slocum Jr., 2007;Bockstedt, Druehl, & Mishra, 2015).…”
Section: Discussionmentioning
confidence: 55%